2021
DOI: 10.1002/bin.1845
|View full text |Cite
|
Sign up to set email alerts
|

Do children who exhibit food selectivity prefer to save the best (bite) for last?

Abstract: Preference for patterns of outcomes that improve over time is termed negative time preference, in economics. In lay terms, this concept equates to "saving the best for last. " Generally, adults tend to prefer to postpone their more preferred outcomes when options are presented as a sequence of events.Event sequencing seems particularly relevant for children who exhibit food refusal or selectivity. Preference for the sequencing of bites when an array involved preferred and relatively non-preferred foods was eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It should be noted that a selection of an initial link in a concurrent‐chains arrangement is only a potential indicator of preference (Ferguson et al, 2022). Other variables may influence choice, such as a preference to experience nonpreferred conditions before more preferred conditions (e.g., Borrero et al, 2022; Ferguson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that a selection of an initial link in a concurrent‐chains arrangement is only a potential indicator of preference (Ferguson et al, 2022). Other variables may influence choice, such as a preference to experience nonpreferred conditions before more preferred conditions (e.g., Borrero et al, 2022; Ferguson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In an applied study, among a small sample of children who exhibit food selectivity, Borrero et al. (2021) recently demonstrated that one of 4 children exhibited a negative time preference—in this case, a preference to start with the least preferred food and progress to the most preferred food. It is possible that the MSWO arrangement might be perceived as an opportunity to select the order in which a sequence of outcomes is experienced.…”
Section: Introductionmentioning
confidence: 99%